BOOK REVIEW The Bloomsbury Handbook of Montessori Education - Claudine Campanelli (University of Kansas, 2023)
The Bloomsbury Handbook of Montessori Education is the first comprehensive collection of scholarly work that spans the spectrum of Montessori education, including historical, political, geographic, pedagogical, scientific, and cultural perspectives. It offers different entry points for those interested in various aspects of Montessori education-advocates, researchers, academics, parents, and teacher educators-to expand their current knowledge about the Montessori pedagogy and movement. The handbook approaches known ideas with an interdisciplinary lens. Maria Montessori's critical writings and radical approaches cemented her legacy. Now, nearly 115 years after her first publication, essential dialogues and critical reflections are emerging about complex social issues in the context of Montessori education. These dialogues recognize the strengths and limitations of the Method as well as the harmful and disrespectful ways Montessori education has entered different communities, countries, and Indigenous lands.